In vivo models of occupational asthma due to low molecular weight chemicals. Issue 8 (August 1995) - Hayes, J P; Taylor, A J Newman
Abstract : The aim was to review the development of in vivo models of asthma due to low molecular weight chemicals, in particular, those aspects that may be important to the understanding of occupational asthma in humans.